Surgical management of rectal prolapse in ostrich chicks (Struthio camelus) - Bishnu Prasad Adhikari; B Pratima; K Kedar (International Journal of Veterinary Science and Research - Peertechz Publications, 2022)
Out of 300 ostrich chicks imported from South Africa, five chicks of age two months faced rectal prolapse problems at once in the Ostrich Farm Private Limited Rupandehi, Nepal. The feather around the red protruded mass was removed and the protruded mass was cleaned with normal saline. The protruded mass was pushed with gentle pressure and corrected through surgical correction. A blood sample was taken for the analysis of the Hematological profile and the fecal sample was observed under the microscope through floatation and sedimentation techniques. On the fecal examination, no parasites were found. Feed management was done for the first day and Calcium with vitamins and other minerals was given. On the next day, two birds having small protruded masses were recovered. The protruded mass of the next three chicks was restored. Local anesthesia was given with 2ml 2%xylocaine solution around the vent region. Purse string suture is done with silk thread around the anal orifice. Blood serum examination reveals that severe low level of calcium i.e. 6.7,7.1,6.5,6.8,6.9 respectively in all 5 ostrich chicks which should be in the normal range of 9-24. As per my case study, the main cause of this prolapse is the low calcium level, the low fiber in the diet and cold stress due to the winter season.